Putting the ‘Art’ Into the ‘Art of Medicine’: The Under-Explored Role of Artifacts in Placebo Studies - Bernstein, Michael H.; Locher, Cosima; Kube, Tobias; Buergler, Sarah; Stewart-Ferrer, Sif; Blease, Charlotte (Frontiers in Psychology, 2020)
Physical environmental factors – or ‘artifacts’ – are linked to healthcare outcomes in the field of social psychology. However, the role of artifacts remains rarely examined in the burgeoning discipline of placebo studies. In this paper, we argue that a careful consideration of artifacts – such as provider clothing and office décor – may carry significant potential in eliciting placebo effects in clinical settings. We discuss three potential mechanisms by which artifacts may enhance or diminish placebo (or nocebo) effects: classical conditioning, response expectancy, and mindsets. We propose testable hypotheses and conclude by providing innovative research designs that might help to better advance this novel research agendum.